To find the y-value that corresponds to the x-value of -1 for the function \( f(x) = 2x^2 - 2x \), we will substitute \( x = -1 \) into the function:
\[ f(-1) = 2(-1)^2 - 2(-1) \]
Calculating this step by step:
-
Compute \( (-1)^2 \): \[ (-1)^2 = 1 \]
-
Now multiply by 2: \[ 2 \times 1 = 2 \]
-
Next, compute \( -2(-1) \): \[ -2 \times -1 = 2 \]
-
Combine both results: \[ f(-1) = 2 + 2 = 4 \]
Thus, the y-value corresponding to the x-value of -1 is \( 4 \).
Summary
The y-value at \( x = -1 \) is \( 4 \).